Diagnostic Test for Estimation of Plasma Volume on Assessment of Congestive Status in Acute Heart Failure Patients at Saiful Anwar General Hospital - Pamuna, Oktafin Srywati; Prasetya, Indra; Astiawati, Tri; Rohman, Mohammad Saifur; Kurnianingsih, Novi (Universitas Brawijaya, 2023)
BackgroundHeart failure is a severe health issue with high death and morbidity rates globally, including in Indonesia. Congestion is the main symptom of acute heart failure. B-type natriuretic peptide (BNP) and N-terminal pro-B-type natriuretic peptide (NT-pro BNP) are well-known markers to confirm the condition. Plasma volume estimation (ePVS)is one of the procedures currently being developed to assess a patient's congestive status at a lower cost. MethodsThis is descriptive observational research with a cross-sectional study method that included all patients with acute heart failure between May 2019-February 2022. Baseline characteristics, medication history, and echocardiography were also included in the statistical analysis. We used univariate and multivariate analysis to assess the effect of each variable on the patient's congestive condition. A diagnostic test of plasma volume estimation was carried out using Receiver Operating Characteristics (ROC) Analysis compared to NT pro-BNP as the gold standard. Results A total of 506 subjects were diagnosed with acute heart failure at Dr. Saiful Anwar Malang Hospital, who met the inclusion and exclusion criteria. The mean age was older in congestive patients with 62.5% being male. Patients with congestive conditions have a lower ejection fraction with a higher estimated right atrial pressure from echocardiography. The estimation plasma volume status was also higher in congestive conditions (6,90 vs 3,5). The ePVS from ROC analysis has a good diagnostic value with a sensitivity of 91, 7% and specificity of 92,6%. ConclusionThe estimation of plasma volume status has a good sensitivity and specificity value to assess congestive status in patients with acute heart failure who are fluid-overloaded.